O programa minha casa minha vida : uma análise dos impactos na cidade de Uberlândia - MG - Moreira, Camilla Fernandes (2013)
The present paper aims to discuss the Minha Casa Minha Vida program, deployed under Lula s government. The foundational theoretical logic is analyzed, as well as the characteristics of the economic system and the assumed political bias. The debate on public policies, State, government, civil society, social movements is promoted. The geographic cut brings out the development of that program in the city of Uberlândia, located in the Minas Gerais s region of Triângulo Mineiro. Specific features of the county are related to national characteristics, taking into account the difference between the deficit and housing demand, the tracks of care provided by the program and its efficiency in terms of reducing housing shortage. The option for the term demand aims to list beyond the precise numbers of the deficit, the quality of buildings and social facilities available. Thus, the analysis allows an evaluation at a greater degree than the mere exposure of data devoid of content related and indispensable.